Answer:
1. g(x)=2x+1-3 --> g(x)=2x-2, which is also y=2x-2, so you can graph it.
Explanation:
Question 1: If f(x) = 2x+1, then you can see that all you have to do is substitute the equation for f(x) into the g(x) equation because g(x)= f(x)-3. So, if you substitute it, the equation will be g(x) = (2x+1) -3, then you just solve the rest of the equation. Put it into slope intercept form, y=mx+b, and then graph the equation.
Sorry, I don't really understand number 2 myself, so hopefully I could help with he first one.